VD_FINDINFO Arrêt / 2018 / 890 vom 30. Oktober 2018 - VD Tribunal cantonal (2018)
INTERNATIONAL, DROIT DE DÉTERMINER LE LIEU DE RÉSIDENCE, COMPÉTENCE RATIONE LOCI | 306 al. 2 CC, 308 al. 1 CC, 310 CC, 3 RCur